2009
DOI: 10.1111/j.1365-2613.2008.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological abnormalities of prolonged alloxan‐induced diabetes mellitus in rabbits

Abstract: The objective of this study was to investigate the prolonged complications of untreated diabetes on histomorphology of rabbits. Diabetes mellitus was experimentally induced in one group of New Zealand white male rabbits by intraperitoneal administration of four doses of alloxan @ 80 mg/kg b.w. at weekly intervals following 12 h fasting. Other group of rabbits served as healthy controls that received isotonic saline in a similar manner. The establishment of diabetes mellitus was confirmed by fasting blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
3
16
1
Order By: Relevance
“…The liver plays a significant role in maintaining glucose and fat metabolism [37]. It is reported that some degenerative changes in hepatocyte are lipolysis and vacuolation [31,33,38]. Our study observed, similar to other studies, lipid accumulation in liver due to degenerative changes and fat vacuoles in the cytoplasm of hepatocytes (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The liver plays a significant role in maintaining glucose and fat metabolism [37]. It is reported that some degenerative changes in hepatocyte are lipolysis and vacuolation [31,33,38]. Our study observed, similar to other studies, lipid accumulation in liver due to degenerative changes and fat vacuoles in the cytoplasm of hepatocytes (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Hystopathological examination of the pancreas in the diabetic group (Fig. 3c-d) indicated the mononuclear cell infiltration of interlobular septum and vacuolizations depended on glycogen degeneration in the ductal epithelium and islets of Langerhans, in similar to previous studies [31][32][33].…”
Section: Discussionsupporting
confidence: 63%
“…Diabetic rabbits are known to exhibit myocardial fibrosis1314. Therefore, in this study, we established a diabetic rabbit model and continuously observed the changes in cardiac function and the degree of diffuse interstitial fibrosis.…”
mentioning
confidence: 99%
“…2001; Sochor et al. 1979; Mir & Darzi 2009). Retinopathy seems to be a consequence of glucose toxicity and increased oxidative stress.…”
mentioning
confidence: 99%